Environmental Compensation Effect and Synergistic Mechanism of Optimized Nitrogen Management Increasing Nitrogen Use Efficiency in Indica Hybrid Rice - Zhou, Wei; Yang, Zhiping; Wang, Tao; Fu, Yong; Chen, Yong; Hu, Binhua; Yamagishi, Junko; Ren, Wanjun (Frontiers in Plant Science, 2019)
Modern rice cultivation relies heavily upon inorganic nitrogen fertilization. Effective fertilizer management is key to sustainable agricultural development. Field and pot trials were conducted in 2014-2016, including a 15N-labeled urea pot experiment (2014) to investigate mechanism by which optimized nitrogen fertilizer application (OFA) increases nitrogen utilization efficiency (NUE). Results showed that the applied nitrogen recovery efficiencies with OFA were 71.71%, 110.17%, and 51.38% higher than those obtained with traditional nitrogen fertilizer application (TFA) in 2014, 2015, and 2016, respectively. These improvements are attributed mainly to the high recovery efficiency rates derived from spikelet-developing and spikelet-promoting fertilizer applications at the jointing stage and 15-20 d after jointing. Under OFA, the amount of nitrogen fertilizer applied at the early stages was half that used in TFA, which not only promoted the absorption of soil nitrogen, but also reduced nitrogen loss to the environment, as the NUE of basal and tillering fertilizer was only about 22%. Nitrogen applied during the panicle differentiation stage increased the expression of ATM1;1, a NH4+ transporter in roots. This effect significantly improved the uptake of nitrogen derived from fertilizer from jointing to heading stage. Up-regulation of the expression and activity of GS and GOGAT at the panicle differentiation and grain-filling stages promoted nitrogen translocation from vegetative to reproductive organs. The uptake of nitrogen derived from fertilizer increased from 22.51% in TFA to 35.58% in OFA. Nevertheless, rice absorbs most of the nitrogen it requires from the soil. The OFA treatment could effectively utilize the environmental compensation effect, promote the absorption and transport of nitrogen, and ultimately lead to improvement in NUE. Future research should aim to understand the soil nitrogen supply capacity in order to apply nitrogenous fertilizer in such a way that it sustains the nitrogen balance.